Implementing of Education Supervision at School of SDN 112304 Panigoran - Ahmadi Hamsa; Chandra Winata; Nurul Zahara Bancin; Puspita Dewi; Sri Mulyani; Tia Pratiwi; Inom Nasution (Universitas Muhammadiyah Enrekang, 2022)
Supervision is supervision of the implementation of educational technical activities in schools, not just physical supervision of physical materials. Supervision is supervision of academic activities in the form of teaching and learning processes, supervision of teachers in teaching, supervision of situations that cause them. Supervision is one of the principal's functions to improve the quality and professionalism of teachers in carrying out teaching. In connection with the importance of school supervision activities related to improving the quality of teachers in particular and improving the quality of education in general. Supervision has the aim of providing services and assistance to improve the quality of student learning, not only improving teaching abilities but also developing the potential of teacher quality. Supervisors must be keen to read the problem, analyze, describe the causal factors and matters related to it, thoroughly present the problems encountered and the steps that must be taken as an effective solution.